Adolescents' Domain-Specific Self-Concepts of Ability Predict Their Domain-Specific Causal Attributions: A Longitudinal Study - Clem, Anna-Leena; Aunola, Kaisa; Hirvonen, Riikka; Määttä, Sami; Nurmi, Jari-Erik; Kiuru, Noona (Merrill-Palmer Quarterly, 2018)
This study investigated longitudinal associations between mathematics- and literacy-related causal attributions and self-concepts of ability among Finnish adolescents (N = 237). Questionnaires were administered to adolescents in Grades 7 and 9 to obtain information on their causal attributions and self-concepts of ability. The results showed that adolescents attributed their successes and failures in a self-consistent way. Specifically, self-concepts of ability predicted subsequent causal attributions in both school subjects. In mathematics, a higher self-concept of ability contributed to more self-enhancing and self-protective attributions. However, in both school subjects, a lower self-concept of ability contributed to more maladaptive attributions.